(untitled) (Scientific journal of the Fergana State University, 2024)
This article explores the significance of dyslexia in educational processes. The research examines the importance of reading in modern society and investigates the issue of dyslexia within the context of various scientific disciplines. The study analyzes the physiological, psychological, linguistic, and social aspects of reading, as well as its cultural impact and the communicative relationships between authors and readers. The article discusses approaches aimed at enhancing students’ reading skills by understanding the social, psychological, and pedagogical consequences of dyslexia. The research also highlights various factors that affect the reading process and instances of dyslexia. To deeply understand the conditions of dyslexia, the physiological, psychological, and semiotic aspects of the reading process are examined. The article also presents new methodological approaches to describing the processes of reading and writing. The importance of scientific approaches and practical strategies for solving problems related to dyslexia is emphasized. The results offer various didactic and therapeutic methods that can be used to address dyslexia-related issues. The processes of explaining and solving these problems through speech therapy and pedagogical methods are also described in the article.